Artificial Channels in an Infectious Biofilm Created by Magnetic Nanoparticles Enhanced Bacterial Killing by Antibiotics. Issue 39 (6th August 2019) - Quan, Kecheng; Zhang, Zexin; Chen, Hong; Ren, Xiaoxiang; Ren, Yijin; Peterson, Brandon W.; van der Mei, Henny C.; Busscher, Henk J.
Abstract: The poor penetrability of many biofilms contributes to the recalcitrance of infectious biofilms to antimicrobial treatment. Here, a new application for the use of magnetic nanoparticles in nanomedicine to create artificial channels in infectious biofilms to enhance antimicrobial penetration and bacterial killing is proposed. Staphylococcus aureus biofilms are exposed to magnetic‐iron‐oxide nanoparticles (MIONPs), while magnetically forcing MIONP movement through the biofilm. Confocal laser scanning microscopy demonstrates artificial channel digging perpendicular to the substratum surface. Artificial channel digging significantly (4–6‐fold) enhances biofilm penetration and bacterial killing efficacy by gentamicin in two S. aureus strains with and without the ability to produce extracellular polymeric substances. Herewith, this work provides a simple, new, and easy way to enhance the eradication of infectious biofilms using MIONPs combined with clinically applied antibiotic therapies. Abstract : A novel application of magnetic nanoparticles is described in which magnetic nanoparticles are used to create artificial channels in infectious biofilms. Artificially dug channels relieve the barrier posed by the biofilm matrix toward antibiotic penetration to enhance eradication of the biofilm. Since magnetic nanoparticles are clinically used, this new application will be relatively easy to translate to clinical practice.